Expanding role of deoxyribonucleic acid-sensing mechanism in the development of lifestyle-related diseases - Nishimoto, Sachiko; Sata, Masataka; Fukuda, Daiju (Frontiers in Cardiovascular Medicine, 2022)
In lifestyle-related diseases, such as cardiovascular, metabolic, respiratory, and kidney diseases, chronic inflammation plays a causal role in their pathogenesis; however, underlying mechanisms of sterile chronic inflammation are not well-understood. Previous studies have confirmed the damage of cells in these organs in the presence of various risk factors such as diabetes, dyslipidemia, and cigarette smoking, releasing various endogenous ligands for pattern recognition receptors. These studies suggested that nucleic acids released from damaged tissues accumulate in these tissues, acting as an endogenous ligand. Undamaged DNA is an integral factor for the sustenance of life, whereas, DNA fragments, especially those from pathogens, are potent activators of the inflammatory response. Recent studies have indicated that inflammatory responses such as the production of type I interferon (IFN) induced by DNA-sensing mechanisms which contributes to self-defense system in innate immunity participates in the progression of inflammatory diseases by the recognition of nucleic acids derived from the host, including mitochondrial DNA (mtDNA). The body possesses several types of DNA sensors. Toll-like receptor 9 (TLR9) recognizes DNA fragments in the endosomes. In addition, the binding of DNA fragments in the cytosol activates cyclic guanosine monophosphate (GMP)-adenosine monophosphate (AMP) synthase (cGAS), resulting in the synthesis of the second messenger cyclic GMP-AMP (cGAMP). The binding of cGAMP to stimulator of interferon genes (STING) activates NF-κB and TBK-1 signaling and consequently the production of many inflammatory cytokines including IFNs. Numerous previous studies have demonstrated the role of DNA sensors in self-defense through the recognition of DNA fragments derived from pathogens. Beyond the canonical role of TLR9 and cGAS-STING, this review describes the role of these DNA-sensing mechanism in the inflammatory responses caused by endogenous DNA fragments, and in the pathogenesis of lifestyle-related diseases.